2008
DOI: 10.1208/s12249-008-9134-9
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Small Pores in Microcrystalline Cellulose for Controlling Water Distribution during Extrusion–Spheronization

Abstract: Abstract. The purpose of this research was to investigate the effects of particle size on the wet massing behavior of microcrystalline cellulose (MCC). In this study, a series of six fractionated MCC grades were customized and specially classified to yield different particle size varieties of the standard grade, Comprecel M101. All seven MCC grades were extensively characterized for the physical properties and wet massing behavior using mixer torque rheometry. Effects of MCC physical properties on the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This result, together with the observation that MCC particle sizes did not change noticeably on squeeze flow testing, indicate that the sponge model -albeit a rubber sponge picture -is more appropriate for the MCC interaction with water. These results are consistent with the observations of Soh et al (2008), who classified their pore size distributions into two types, as either greater than or less than 10 m. They observed that the wet massing consistency of six different MCC grades correlated strongly with the amount of small pores present in the native powder. They did not measure pore size distributions following contact with the liquid binder, and did not consider liquids other than water.…”
Section: Microstructuresupporting
confidence: 91%
See 1 more Smart Citation
“…This result, together with the observation that MCC particle sizes did not change noticeably on squeeze flow testing, indicate that the sponge model -albeit a rubber sponge picture -is more appropriate for the MCC interaction with water. These results are consistent with the observations of Soh et al (2008), who classified their pore size distributions into two types, as either greater than or less than 10 m. They observed that the wet massing consistency of six different MCC grades correlated strongly with the amount of small pores present in the native powder. They did not measure pore size distributions following contact with the liquid binder, and did not consider liquids other than water.…”
Section: Microstructuresupporting
confidence: 91%
“…The success of MCC-water combinations as a filler in extrusion spheronisation has been explained by two qualitative microstructural models, namely the: (i) 'sponge' (Fielden et al, 1988;Ek and Newton, 1998;Soh et al, 2008) and (ii) the "crystallite-gel" (Kleinebudde, 1997). These differ in the mechanism by which water is held by the MCC.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury contact angle (φ), surface tension (γ), and density were taken as 130°, 485 dynes/cm, and 13.53 g/mL, respectively (5). Approximately 75% of the penetrometer volume was filled with pellets from the 850-1,000-μm size fraction of each batch.…”
Section: Micromeritic Propertiesmentioning
confidence: 99%
“…Small particles that are more heterogeneous in size could achieve closer packing. 19 The close packing of particles results in particles being stacked on top of one another causing problem in the formation of the tablet during compression. To enhance the flow of granules with different concentration of MCC per formulations, 1% magnesium stearate was added as a lubricant to each formulation.…”
Section: Evaluation Of Tabletsmentioning
confidence: 99%